Interactive Industrial Robot Programming for the Ceramic Industry. (16th October 2013) - Veiga, Germano; Malaca, Pedro; Cancela, Rui
This paper presents an interactive programming method for programming industrial robots in ceramic applications. The main purpose was to develop a simple but flexible programming system that empowers the user with product driven programming without compromising flexibility. To achieve this flexibility, a two step hybrid programming model was designed: first the user sketches the desired trajectory in a spatial augmented reality programming table using the final product and then relies on an advanced 3D graphical system to tune the robot trajectory in the final workcell. The results measured by the end-user feedback show that a new level of flexibility was reached for this type of application.